Synthesis, characterization, antimicrobial and antibiofilm activity, and molecular docking analysis of NHC precursors and their Ag-NHC complexes. Issue 42 (14th October 2021) - Üstün, Elvan; Şahin, Neslihan; Çelik, Cem; Tutar, Uğur; Özdemir, Namık; Gürbüz, Nevin; Özdemir, İsmail
Abstract : A series of novel silver(i )-NHC complexes are synthesized and characterized. The anticandidal activity of some complexes was found to be similar to that of Flucanozol. Abstract : Microorganisms attach to surfaces and interfaces and form biofilms which create a sheltered area for host cell response. Therefore, biofilms provide troubles in fields such as medicine, food, and pharmaceuticals. Inhibition of formation of biofilms through hindering of quorum sensing could be a method for the production of new generation antibiotics. In this study, four new benzimidazole type NHC precursors (1-allyl-3-benzyl-5, 6-dimethylbenzimidazolium chloride, 1-allyl-3-(2, 4, 6-trimethylbenzyl)-5, 6-dimethylbenzimidazolium chloride, 1-allyl-3-(2, 3, 5, 6-tetramethylbenzyl)-5, 6-dimethylbenzimidazolium chloride, and 1-allyl-3-(2, 3, 4, 5, 6-pentamethylbenzyl)-5, 6-dimethylbenzimidazolium chloride and Ag-NHC complexes of these molecules were synthesized and characterized by elemental analysis, FT-IR spectroscopy, 1 H, and 13 C{ 1 H} NMR spectroscopy, LC-MS, and single crystal crystallography. Antimicrobial and biofilm formation inhibition activities of the molecules were evaluated. In addition, the activities of the molecules were examined in detail by molecular docking analysis. According to the results obtained, higher activity was achieved with the complex molecules when compared with the benzimidazole derivative ligands.